Development of a PCR method for detection of thromboxane synthase gene / Roihanah Rahmat - Rahmat, Roihanah (2009)
Thromboxane synthase gene (TBXAS 1), converts prostaglandin H2 into thromboxane A2, a potent vasoconstrictor and inducer of platelet aggregation. Thromboxane A2 has been implicated in modulating cell cytotoxicity tumor growth and metastasis. The aim of this study is to develop and validate a simple PCR based method to detect the allelic variance of thromboxane synthase gene. The primers were designed according to the gene sequence. Polymerase Chain Reaction using first and second set of primers was done to amplify the sequence of TBXASl. Besides, DNA collection methods arise from blood samples and buccal samples also successfully done in detection of wild-type and mutated alleles respectively by using common reverse primer plus wild-type forward primer and mutant forward primer. Based on the result of this study, it can be concluded that the amplification process is successful based on the correct band size obtained. From the PCR product, there were some bands that shows heterozygous and homozygous for allelic variance in TBXASl gene. For further confirmation, the PCR product that was obtained in this study would be sent for sequencing and compared with published sequences.